Breeding aflatoxinresistant maize lines using recent advances in technologies a review - Brown, R.; Menkir, A.; Chen, Z.; Bhatnagar, D.; Yu, J.; Yao, H.; Cleveland, T. (Informa UK Limited, 2013)
Aflatoxin contamination caused by Aspergillus flavus infection of corn is a significant and chronic threat to corn being used as food or feed. Contamination of crops at levels of 20 ng g–1 or higher (as regulated by the USFDA) by this toxin and potent carcinogen makes the crop unsalable, resulting in a significant economic burden on the producer. This review focuses on elimination of this contamination in corn which is a major US crop and the basis of many products. Corn is also “nature’s example” of a crop containing heritable resistance to aflatoxin contamination, thereby serving as a model for achieving resistance to aflatoxin contamination in other crops as well. This crop is the largest production grain crop worldwide, providing food for billions of people and livestock and critical feedstock for production of biofuels. In 2011, the economic value of the US corn crop was US$76 billion, with US growers producing an estimated 12 billion bushels, more than one-third of the world’s supply. Thus, the economics and significance of corn as a food crop and the threat to food safety due to aflatoxin contamination of this major food crop have prompted the many research efforts in many parts of the world to identify resistance in corn to aflatoxin contamination. Plant breeding and varietal selection has been used as a tool to develop varieties resistance to disease. This methodology has been employed in defining a few corn lines that show resistance to A. flavus invasion; however, no commercial lines have been marketed. With the new tools of proteomics and genomics, identification of resistance mechanisms, and rapid resistance marker selection methodologies, there is an increasing possibility of finding significant resistance in corn, and in understanding the mechanism of this resistance.